МАТЕМАТИЧНА МОДЕЛЬ ХВИЛЬОВИХ ПРОЦЕСІВ У ДВООБМОТКОВИХ ТРАНСФОРМАТОРАХ - Сегеда, М.С.; Черемних, Є.В.; Гоголюк, П.Ф.; Мазур, T.A.; Близнак, Ю.В. (Інститут електродинаміки НАН України, Київ, 2020)
A mathematical model has been developed to study the wave processes of two-winding transformers, taking into account the electromagnetic connections between the turns of the winding and between the windings. To solve differential-integral equations in partial derivatives, a method of separation of variables is proposed. References 12, figures 2.